2011
DOI: 10.1289/ehp.1002114
|View full text |Cite
|
Sign up to set email alerts
|

An Emerging Role for Epigenetic Dysregulation in Arsenic Toxicity and Carcinogenesis

Abstract: BackgroundExposure to arsenic, an established human carcinogen, through consumption of highly contaminated drinking water is a worldwide public health concern. Several mechanisms by which arsenical compounds induce tumorigenesis have been proposed, including oxidative stress, genotoxic damage, and chromosomal abnormalities. Recent studies have suggested that epigenetic mechanisms may also mediate toxicity and carcinogenicity resulting from arsenic exposure.ObjectiveWe examined the evidence supporting the roles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
229
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 316 publications
(235 citation statements)
references
References 128 publications
(172 reference statements)
5
229
0
1
Order By: Relevance
“…56 Aberrant DNA methylation levels have been found to be associated with the onset and progression of adult-onset metabolic diseases. 3,4,13,56,57 Thus, we can speculate that the higher Dnmt3b expression and the temporarily higher DNA methylation state, as that Dnmt3b mRNA receives posttranscriptional regulation along with the time of day. Further study based on these hypotheses will be required to unveil the mechanism of diurnal variation of Dnmt3b transcription.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…56 Aberrant DNA methylation levels have been found to be associated with the onset and progression of adult-onset metabolic diseases. 3,4,13,56,57 Thus, we can speculate that the higher Dnmt3b expression and the temporarily higher DNA methylation state, as that Dnmt3b mRNA receives posttranscriptional regulation along with the time of day. Further study based on these hypotheses will be required to unveil the mechanism of diurnal variation of Dnmt3b transcription.…”
Section: Discussionmentioning
confidence: 99%
“…3 Some agents are known to alter the DNA methylation state by changing the level of expression of Dnmt and/or by modifying the enzymatic activity of DNMT. 3,13 Transcription of Dnmt3a and Dnmt3b is reported to be regulated by the ubiquitous transcription factors specific protein 1 (Sp1) and Sp3.…”
Section: Diurnal Variations Inmentioning
confidence: 99%
“…The mechanism underlying arsenic toxicity is believed to be due to methyl depletion-induced aberrant DNA methylation, and excessive ROS generation and subsequent oxidative cell injury. [40][41][42]45 Niacin Niacin (nicotinic acid and nicotinamide) is a water-soluble vitamin and a common methyl consumer. 46 Dietary nicotinic acid is derived from plant foods, while nicotinamide is derived from animal foods and typically used for food fortification.…”
Section: Arsenicmentioning
confidence: 99%
“…Excessive methyl consumer-induced methyl depletion may affect DNA methylation status, as observed in arsenic exposure. 45 Moreover, some secondary factors may contribute substantially to the development of the disease. These factors include: (1) other ROS-generating xenobiotics or compounds, such as alcohol, (2) chronic mental stress and (3) lifestyle-related factors such as high fat intake, low vegetable intake and decreased skin functions (primarily sweat elimination) (Figure 1).…”
Section: Proposed Mechanism For the Effects Of Methyl Consumersmentioning
confidence: 99%
“…A number of studies have demonstrated that iAs exposure induces global and gene-specific post-translational histone modifications such as reduction of acetylation in histone H3 and H4: loss of H4Lys 16 10 and H2AX phosphorylation, and decreases in H2B ubiquitination (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26).…”
mentioning
confidence: 99%